UJI AKTIVITAS ANTIBAKTERI MASKER GEL PEEL-OFF EKSTRAK DAUN KEPEL (Stelechocarpus burahol) TERHADAP Propionibacterium acnes - Ali Nofriyaldi; Lidia Novianty Afifah; Lina Rahmawati (Jurnal Insan Farmasi Indonesia, 2026)
Acne is a common skin disorder caused by Propionibacterium acnes. Kepel leaves (Stelechocarpus burahol) contain secondary metabolites, including flavonoids, alkaloids, saponins, and tannins, which possess antibacterial potential. This study aimed to formulate a peel-off gel mask containing ethanolic extract of Kepel leaves and evaluate its antibacterial activity against Propionibacterium acnes. The research included extraction using 96% ethanol, phytochemical screening, formulation of peel-off gel masks, physical evaluation, and antibacterial testing using the agar diffusion method. Three formulations containing different extract concentrations were prepared: F1 (1%), F2 (3%), and F3 (5%). All formulations showed acceptable physical characteristics for topical preparations, including homogeneity, pH, viscosity, drying time, and stability. Antibacterial testing demonstrated concentration-dependent inhibitory activity, with inhibition zones of 14.64 mm, 19.11 mm, and 21.10 mm for F1, F2, and F3, respectively. Statistical analysis revealed significant differences among groups (p < 0.001). Although the antibacterial activity of all formulations was lower than 1% clindamycin, the 5% extract formulation exhibited the strongest inhibitory effect against Propionibacterium acnes. These findings indicate the potential of Kepel leaf extract as a natural antibacterial agent in topical anti-acne formulations.